Catalytic Intermolecular Dicarbofunctionalization of Styrenes with CO2 and Radical Precursors. (1st August 2017) - Yatham, Veera Reddy; Shen, Yangyang; Martin, Ruben
Abstract: A redox‐neutral intermolecular dicarbofunctionalization of styrenes with CO2 at atmospheric pressure and carbon‐centered radicals is described. This mild protocol results in multiple C−C bond‐forming reactions from simple precursors in the absence of stoichiometric reductants, thus exploiting a previously unrecognized opportunity that complements existing catalytic carboxylation events.